Isolation and identification artemisinine from product of endophyte microbe cultivation from Artemisia annua. [studies on endophytic microbes of Artemisia spp. (3)] - Simanjuntak, Partomuan; ., Bustanussalam; Otovina, Dian Malini; Rahayuningsih, M.; Said, E.G. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Isolation of the biotransformation product artemisinine from endophitic bacteria is a new alternative for the production of the multidrugresistant antimalaria compounds. The bacteria strain, AT 12, has been proved particularly potential as an artemisinin source.This working was carried out to isolate and to identify the biotransformation product artemisinin as an antimalarial active compound from endophitic bacteria strains of Artemisia annua. The IR spectrum exhibited the characteristic bands for Î´-lactone (1750-1735 cm-1, 1250-1111 cm-1) and endoperoxide function ( 1115 cm-1, 890-830 cm-1). As a result, the GC-MS gave a positively identification for the majority of GC peaks. The mass spectrum of the peak (Rt 27.94 min) has a molecular ion of artemisinin with one hydrogen loss at m/z 281, representing (M+ - 1).Keywords: Artemisia spp. Artemisia annua, Endophytic, Artemisinine, sesquiterpene